Pengaruh Kepemimpinan, Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Tenaga Kesehatan - Idho Gusti Putra (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine how much influence the variables of leadership, work discipline and job satisfaction simultaneously and partially on the performance of health workers at the Muara Siberut Health Center, Mentawai Islands Regency, South Siberut District, using data collection methods in the form of questionnaires and the analysis method used is regression. multiple linear. The results showed that the variables of leadership, work discipline and job satisfaction had a significant effect on the performance of health workers at the Muara Siberut Health Center, Mentawai Islands Regency, South Siberut District, marked with an R value of 0.707 and an Adjusted R Square of 0.479. This shows that there is a strong relationship between leadership, work discipline and job satisfaction on the performance of health workers at the Muara Siberut Health Center, Mentawai Islands Regency, South Siberut District by 47.9% while the remaining 52.1% is influenced by other factors outside this study. Partially, the variables of leadership, work discipline and job satisfaction have a significant effect on the performance of health workers at the Muara Siberut Health Center, Mentawai Islands Regency, South Siberut District.